Triune God : incomprehensible but knowable : the philosophical and theological significance of St Gregory Palamas for contemporary philosophy and theology - Athanasopoulos, Constantinos (Cambridge Scholars Publishing, 2016)
The 13th and 14th centuries represented the most productive and influential period in the history of philosophy and theology in the West. A parallel and less influential (for the West) proliferation of arguments and theories took place in the East, at the same time, as a result of the defence of the Hesychastic movement offered by St Gregory Palamas and his followers. The papers brought together in this volume discuss the importance of Palamite ideas for the understanding of God in terms of divine energies, and for contemporary approaches to solving perennial problems in science, metaphysics,